Correlation Study on Expression of GST-π Protein in Brain Tissue and Peripheral Blood of Epilepsy Rats Induced by Pilocarpine - 邓学军 贾红 杨志勇 李刚 孙圣刚 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
Previous studies have suggested that glutathione-S-transferase π （GST-π） over-expression in the brain tissue is associated with refractory epilepsy. However, whether the change in GST-π level in the peripheral blood is in line with that in brain tissue remains unknown. This study examined the correlation between GST-π in brain tissue and that in peripheral blood in rat models of pilocarpine-induced refractory epilepsy. The animals were divided into drug-resistant group and drug-responsive group according to the response to anti-epileptic drugs. GST-π expression in brain tissue was immunohistochemically determined, while the expression of GST-π in peripheral blood was analyzed by Western blotting. In the hippocampus and cortex, GST-π was mainly found in the cytoplasm and membrane of neurons, and the GST-π expression level was higher in drug-resistant group than in the drug-responsive group and saline control group （P〈0.05）. Moreover, there was no significant difference between responders and saline control animals （P〉0.05）. The change in expression of GST-π in peripheral blood showed the same pattern as that in brain tissues, suggesting GST-π might contribute to drug resistance in epilepsy. Importantly, the GST-π over-expression in peripheral blood could be used as a marker for resistance to anti-epileptic agents.